Constipation in Parkinson's Disease - Quigley, Eamonn M. M. (Seminars in Neurology, 2023)
Constipation is one of the most common gastrointestinal features of Parkinson's disease (PD), occurring in over 50% of all PD patients during the course of their disease. Furthermore, constipation is now recognized as an important, prodromal symptom and may predate the onset of the classical motor symptoms by decades. Thereafter, the prevalence and severity of constipation in PD tend to parallel the course of both motor and nonmotor phenomena such as cognitive decline and depression. Difficult defecation (obstructed defecation, dyssynergia) is the primary pathophysiology underlying constipation and likely reflects involvement by the PD process of one or more of the many skeletal muscle groups that are involved in effecting defecation. Management of constipation in PD may be complicated by several patient factors including dysphagia, cognitive impairment, depression, and weak sphincter tone. While the armamentarium available to those who treat constipation, in general, has expanded considerably in recent years, the evidence supporting any therapy in the management of this symptom in PD has remained slim.
Keywords: Parkinson's disease; parkinsonism; constipation; dyssynergia; enteric nervous system; colon transit; prokinetic; prosecretory agents